Effects of Various Drying Times on the Properties of 3D Printed Orodispersible Films - Natália Janigová; Jan Elbl; Sylvie Pavloková; Jan Gajdziok (MDPI AG, 2022)
Orodispersible films are an innovative dosage form. Their main advantages are the application comfort and the possibility of personalization. This work aimed to evaluate the influence of different drying times on the properties of orodispersible films of various thicknesses, prepared in two different semisolid extrusion 3D printing setups. In the first experiment, drying times were dependent on the overall print time of each batch. In the second setup, the drying time was set equal according to the longest one. The evaluated parameters were films' weight uniformity, thickness, moisture content, surface pH, disintegration time, hardness, and tensile strength. Upon statistical comparison, significant differences in the moisture content were found, subsequently affecting the disintegration time. Moreover, statistically significant differences in films' mechanical properties (hardness, tensile strength) were also described, proving that moisture content simultaneously affects film plasticity and related properties. In conclusion, a mutual comparison of the manufactured orodispersible films showed that the drying time affects their physical and mechanical properties. The in-process drying setup was proved to be sufficient while allowing quicker manufacturing.